ANALISIS PENDETEKSIAN HERDING BEHAVIOUR PADA BURSA SAHAM EMERGING DAN DEVELOPED MARKET ASIA (Negara Indonesia, China, Singapura dan Jepang) TAHUN 2012-2016 - Sendy, Hana; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2017)
Herding behaviour is one of investor’s irrasional behaviour that investors make decisions by following other investors' decisions or following a market consensus and tend not to use their own analysis in making their investment decisions. Herding behavior can affect the stability of the stock market because the market index value in the stock market will lead to a new price equilibrium, so it does not reflect the economic condition.This  research  tries  to  detect  whether  there  is  any  herding  behavior  by  investors  in emerging market and developed market, which are Indonesia, China, Singapore and Japan stock exchange. By looking at the relationship between Cross Sectional Absolute Deviation (CSAD) and market return, the herding behavior on the stock market can be known. This study used a quantile regression analysis because detection of herding was done under different conditions of market. Which the condition is market stress normal and high return.The results of this study shows that herding behavior detected on the emerging market which is Indonesia and China stock market on the high return market condition, that means investors on the emerging market stock exchange do herding so it can be concluded investors in emerging  market  has  an  irrational  behavior.  While  herding behaviour  not  detected  on  the developed  market  which  is Japan  an  Singapore  stock  market,  that  means  investors on the developed market country has a rational behavior